Media and Environment: a case study at portuguese television - PadrÃ£o, Joana (Mediterranean Journal of Social Sciences, 2012)
Mass media play a determinant role in the dissemination and construction of social threats and risks. Studies haveshown that public learns a lot of things about science through consuming mass media news. The present paper examines mediadiscourse about the environmental risk and the importance of the environment communication. In order to perform this analysiswe have selected the environmental programs on portuguese television broadcasted between january 2010 and december 2011.This sample of programs has been recorded and viewed in order to select the news we wanted to analysis. We have selected allthe pieces of news that either directly relate to any environmental problem (pollution, climate change, global warmingâ€¦) or referin any other way to the environment and the nature (about the weather, earthquakes, hurricanes or other meteorological event).Qualitative techniques of analysis have been applied, in order to categorize the information, looking for common and divergentdiscourses at some dimensions, such as: causes; consequences; possible solutions; and discourses. The media have toenhance environmental science communication, since within the majority of portuguese public sphere this is the only way ofenvironmental knowledge.